Research of innovative susceptibility of HR management systems in the context of analysis of world and Ukrainian information sources - Diuzhev, V. H.; Boichenko, O. I. (Baltija Publishing, Poland, 2018)
This material is devoted to the analysis of information sources in the field of management of human resource management systems (HRMS) in order to identify trends in their development. Best practices of European and world companies, which can be applied at Ukrainian enterprises, are considered. A comparative analysis of the main indicators of the complexity of reflecting the problems of HR management on the world and Ukrainian databases of electronic resources is made. A number of factors that hamper the growth of research in the field of HRMS are identified; recommendations on activities that will lead to an improvement of the innovative susceptibility (IS) of the HRMS of Ukrainian enterprises are made.
Keywords: industrial enterprises; Human Resource Management Systems; innovative susceptibility